Risk Management Analysis of Information Technology (IT) Asset Security Using ISO 31000 and FMEA - Indira Carisa Dewi, Carisa; Ghea Sekar Palupi (Journal of Education Technology and Information System, 2025)
Information technology assets play an important role in the running of business processes at BPS Kota Mojokerto because information technology assets are one of the important sources of information at BPS Kota Mojokerto. The absence of a structured policy regarding special handling in terms of information technology asset management and the lack of understanding of BPS employees about security and related information technology asset components are one of the causes of potential risks at BPS Kota Mojokerto. The purpose of this study is to identify, assess and mitigate risks related to information technology managed by BPS Kota Mojokerto based on the ISO 31000 and FMEA methods. This research method uses qualitative analysis through in-depth interviews and evaluation of SOP documents and related IT assets. The results of the study identified 58 overall risks to IT assets. It is hoped that the results of the risk management document can be used as a tool for BPS Kota Mojokerto to minimize risks, as well as develop detailed and systematic risk mitigation analysis.